A few words on differentiating magno- and parvocellular contributions to vision on the basis of temporal frequency. (December 2016) - Skottun, Bernt C.
Abstract: A number of authors have proposed that changes in temporal frequency within the range of 0–30 Hz may be used to differentiate contributions from the magno- and parvocellular systems. The present analyses estimate the percentage of active magnocellular cells as a function of frequency based on published cut-off values for magno- and parvocellular cells. These analyses indicate that varying the temporal frequency over the range of 0–30 Hz has little effect upon the percentage of active magnocellular cells. The analyses were also carried out for a series of hypothetical cut-off frequencies and standard deviations of these frequencies for magnocellular cells. The results of these simulations indicate that even large alterations in these values do not alter the above conclusion to a noteworthy extent.